Analysis of Breakdown Characteristics in Nanofluid Insulation Materials with Metal Particle Contamination - Mubarok, Abdul Fattah; Asfani, Dimas Anton; Negara, I Made Yulistya; Fahmi, Daniar; Subekti, Hakim (JAREE (Journal on Advanced Research in Electrical Engineering), 2024)
Optimal insulation in transformers is essential to maintain their performance and reliability. However, insulation-related problems, particularly transformer oil contamination, often result in premature transformer failure. To address this issue, a solution has been proposed in the form of a nanofluid, a mixture of transformer oil, and nanoparticles. This study aims to investigate the impact of metal particle contamination on the breakdown and levitation voltage characteristics of nanofluids as liquid insulating materials. The nanofluids were prepared by mixing mineral oil with Fe3O4 nanoparticles at three different concentrations. Tests were conducted to evaluate the AC breakdown and levitation voltages for various contaminant metal particle sizes. The experimental results demonstrate that contaminant particle size has a significant impact on the breakdown voltage. The nanofluid with a concentration of 0.008% Fe3O4 exhibited superior breakdown voltage performance compared to mineral oil and 0.016% Fe3O4 nanofluid. Furthermore, an increase in the levitation stress was observed as the contaminant particle size increased. The findings of this study emphasize the importance of controlling contamination and selecting the appropriate concentration of nanoparticles to enhance transformer insulation performance. This study also highlights the necessity of monitoring the size of contaminant particles to prevent potential damage. Consequently, this study makes a significant contribution to the advancement of more reliable and efficient transformer insulation technology.